2015
DOI: 10.1016/j.ijsu.2015.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Metastasising pleomorphic adenoma: Systematic review

Abstract: Benign MPA is rare. Metastasis occurs years after the initial PA and is associated with multiple local recurrences. Histologically, MPA retain their benign nature yet demonstrate malignant behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 53 publications
3
74
0
14
Order By: Relevance
“…Ratnasingham reviewed 81 cases reported from 1942 to 2014 in the English language literature (2) and found that the most common sites for metastasizing pleomorphic adenoma were bone (36.6%), lung (33.8%), and cervical lymph nodes (20.1%) and that the local recurrence rate prior to metastasizing pleomorphic adenoma was 72.8% (2). In our case, bone and cervical node metastases were not identified by whole-body contrast enhanced CT or FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ratnasingham reviewed 81 cases reported from 1942 to 2014 in the English language literature (2) and found that the most common sites for metastasizing pleomorphic adenoma were bone (36.6%), lung (33.8%), and cervical lymph nodes (20.1%) and that the local recurrence rate prior to metastasizing pleomorphic adenoma was 72.8% (2). In our case, bone and cervical node metastases were not identified by whole-body contrast enhanced CT or FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for metastasizing pleomorphic adenoma is difficult to quantify because such patients have not been subject to long-term follow-up, and case reports have often been published relatively early after treatment. The 1-year survival rate has been reported to be 80.4%, and the 2-, 3-, and 5-year survival rates have been reported to be 64.7%, 41.2%, and 31.4% (2). The independent prognostic factors are that the metastases are present at a signal site and that the interval between the initial primary tumor presentation and distant metastasis is more than 10 years; the 4-year survival with the former and the latter are reportedly more than 70% and more than 80% (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though it is classified as a benign tumor, PA may undergo malignant transformation into carcinoma ex-pleomorphic adenoma, a risk that is believed to increase with time [1]. Also it can recur after resection; distant metastases have been reported after long time intervals [2,3]. PA often occurs in the major salivary glands, most commonly on the parotid gland [4].…”
Section: Introductionmentioning
confidence: 99%